Synthesis of Oxindoles via SmI2-Promoted Reduction of 2-Nitrophenylacetic Acids - Wang, Pengkai; Zhang, Songlin (Synthesis, 2023)
The reduction of 2-nitrophenylacetic acids to oxindoles promoted by SmI2 is reported for the first time. This reaction involving the reduction of nitro group proceeds through N–O bond cleavage and direct condensation with the neighboring carboxyl group. From a synthetic point of view, a new method for the synthesis of oxindoles in mild neutral conditions is developed.
Keywords: samarium diiodide; single electron transfer reagent; oxindoles